From Athletic Capital to Entrepreneurial Action: How former professional athletes' human capital impacts their entrepreneurial decision-making - Ommen,Eike Christjan; Olk,Markus (2026)
This study examines how the human capital of former professional athletes impacts their entrepreneurial decision-making during the venture creation process. Using Human Capital Theory and the literature on entrepreneurial decision-making, this study explores how the dispositions, knowledge, and networks accumulated through an athletic career shape the reasoning logics through which former athletes create new ventures. The data was collected through a qualitative approach using semi-structured interviews with eleven former professional athletes in Germany who have transitioned into entrepreneurship as a second career, sampled through a combination of purposeful and snowball sampling. During the analysis five aggregated dimensions were developed, athletic human capital formation, sport-derived human capital and its transferability, network and identity as means, decision-making logic in venture creation, and human capital deployment across the venture creation pathway, resulting in a model. These findings demonstrate how athletic human capital functions as the foundational inventory from which athletepreneurs reason under either causal or effectual logic, while the dominant logic shifts across phases of the venture creation process, causal-leaning under forced transition, effectual- dominant at venture identification, and integrated at the functioning venture. The study expands on current theories of entrepreneurial decision-making and athlete career transition, specifically by conceptualising coexistence between causal and effectual logics as phase-structured and proposes practical recommendations for athletes and supporting institutions.
Keywords: Athletepreneur; Entrepreneurial decision-making; Effectuation; Causation; Human Capital Theory; Venture creation process; Athlete career transition; Qualitative research